Radioimmunotherapy - Translational Opportunities and Challenges - Gaipl, Udo S.; Multhoff, Gabriele; Graham Pockley, Alan; Rödel, Franz (Frontiers Media SA, 2020)
Surgery, chemotherapy and radiotherapy remain the three primary approaches for treating the majority of cancers. Although the primary aim of radiotherapy is to inhibit tumor cell proliferation and induce tumor cell death by inducing DNA double-strand breaks, it is also known to have a number of immunological effects, the manipulation of which could enhance clinical efficacy. Recent insights into the immunomodulatory capacity of tumours, and the development of approaches to therapeutically exploit these have prompted the emergence of a range of immunotherapeutic approaches for inducing and enhancing robust, protective anti-tumor immunity. Combining radiotherapy with immunotherapy (radioimmunotherapy) therefore has significant clinical potential. The aim of this Research Topic is to collate primary articles, reviews and opinion pieces on the complex reciprocal relationships between the immune system, tumors and the tumour microenvironment, and the stimulatory and suppressive effects of radiotherapy on innate and adaptive immunity in the pre-clinical and clinical settings.